Chromatographic Purification of Recombinant Nucleocapsid Protein of Nipah Virus from Escherichia Coli Homogenate - Chong, Fui Chin (2010)
The nucleocapsid protein (NCp) of Nipah virus (NiV) expressed in Escherichia coli (E. coli) is antigenic and immunogenic. NCp-NiV is a potential serological antigen that can be used in the diagnosis of NiV infections. The yield of NCp expressed in E. coli is low due to the proteolytic degradation by host endogenous proteases. Therefore, it is important to inhibit the endogenous proteolytic degradation activity and shorten the protein recovery process to avoid or reduce the action of protease on the recombinant NCp. A method to predict the type of potential protease that attacks the NCp-NiV and its potential cleavage sites in E. coli to enhance the recovery of NCp was developed. A bioinformatics tool, PeptideCutter was used to identify potential protease and its cleavage sites from the amino acid sequences deduced from the published DNA sequence of the NCp-NiV. The predicted proteases were serine proteases, hence, a range of serine protease inhibitors were tested to improve the yield of NCp. The yield of NCp was increased by 2-fold after the phenylmethylsulphonyl fluoride (PMSF) supplementation. The downstream processing of the NCp-NiV from clarified E. coli homogenate was investigated. Two types of preparative chromatographic purification in a packed bed column; immobilised metal affinity chromatography (IMAC) and hydrophobic interaction chromatography (HIC) were studied and compared. A direct recovery of recombinant NCp-NiV from unclarified E. coli homogenate based on EBA chromatography was then developed by using the type of chromatography that can obtain high yield of the NCp with high antigenicity. In the IMAC system, HisTrapTM 6 Fast Flow was applied to purify the recombinant histidine-tagged NCp. A histidine hexamer tag was placed at the C-terminus of the NCp and this enabled the purification of NCp by IMAC system. The optimal binding was achieved at pH 7.5 and superficial velocity of 75 cm/h. The bound NCp was successfully recovered by a stepwise elution with a range of imidazole concentration (50, 150, 300 and 500 mM). The NCp was captured and eluted from an inlet NCp concentration of 0.4 mg/ml in a scale-up IMAC packed bed column of Nickel SepharoseTM 6 Fast Flow with the optimized conditions obtained from the scouting method. The purification of histidine-tagged NCp using IMAC packed bed column has resulted a 68.3% yield and a purification factor of 7.94. In the HIC system, ammonium sulfate precipitation experiment was performed and it showed that 15% saturation of the salt was the most suitable concentration for the binding buffer. Batch binding of the NCp was performed using Sepharose™ 6 Fast Flow adsorbents coupling separately with four different types of ligand; phenyl low substitution, phenyl high substitution, butyl and octyl. The phenyl low substitution ligand was selected for subsequent optimization process due to its highest yield and purity of the NCp achieved from the batch binding experiment. The HIC for purification of the NCp was further scaled up using a 10 cm column packed with phenyl low substitution Sepharose™ adsorbent. A recovering yield of 81% of the NCp with a purification factor of 9.3 was achieved from this scaled-up HIC operation. Hence, the HIC adsorbent was used to capture the NCp in an EBA column due to its higher yield and purity obtained in the third chapter than the IMAC purification in the second chapter of this study. DNase was added to reduce the viscosity of feedstock and improve the axial mixing prior to the loading of the feedstock to the EBA column packed with the StreamlineTM HIC adsorbent charged with phenyl. The addition of glycerol to the washing buffer has reduced the volume of washing buffer applied, and thus reduced the loss of the NCp during washing stage. The dynamic binding capacity at 10% breakthrough of 3.2 mg/g adsorbent was achieved at a linear flow velocity of 178 cm/h, bed expansion of two and viscosity of 3.4 mPas. The adsorbed NCp was eluted with the buffer containing a step gradient of salt concentration. The purification of hydrophobic NCp using HIC-EBA column has resulted an 80% yield and a purification factor of 12.5.